Improved physical properties of konjac glucomannan gels by co-incubating composite konjac glucomannan/xanthan systems under alkaline conditions. (September 2020) - Yang, Xi; Li, Anqi; Li, Dan; Li, Xiaofei; Li, Peiyuan; Sun, Lijun; Guo, Yurong
Abstract: Alkali induced konjac glucomannan (KGM) gels have been a popular food item in many Asian nations since ancient times. However, there exist a few drawbacks for this type of gels, including significant syneresis and inferior gel strength, etc . In this study, due to relatively strong alkali resistance, xanthan was selected to be incorporated into KGM sol systems, and the composite KGM/xanthan systems were then allowed to gel by subjecting to a protocol consisting of incubating at 90 °C for 2 h and then cooling to room temperature. It was found that the gelation process consisted of two steps: during incubation at 90 °C, KGM gel network was predominantly formed, and the incorporation of xanthan caused a slower gelling rate of the KGM gel network. In the subsequent cooling process, xanthan synergistically bound with the KGM network, thereby strengthening the composite gels, with the binding process beginning at 60 °C. When the KGM/xanthan ratio was 7:3, the highest gel strength ( 1200 g) of the composite gel was obtained, which is much higher than the pure KGM gel (KGM/xanthan ratio 10:0, and the gel strength was 44 g). Moreover, xanthan addition also decreased the syneresis rate of the composite gels during freeze-thaw treatment. Overall, the present study highlighted an applicable way to tailor the physical properties of KGM gels by co-incubating a composite KGM/xanthan system in the presence of alkali. Graphical abstract: Image 1 Highlights: The gelation process of the composite gels was a two-step process. The presence of xanthan decreased the gelation rate of the KGM gel network. Xanthan addition decreased the syneresis rate of the composite gels. The optimum synergistic ratio shifted to a higher KGM to xanthan ratio.